Dalam perekonomian Indonesia, Usaha Mikro, Kecil, dan Menengah (UMKM) adalah kelompok usaha yang memiliki jumlah paling besar, sebagai garda terdepan UMKM memiliki peranan di Indonesia bahkan ASEAN. Penelitian ini bertujuan untuk menganalisa upaya pengemb - M. Asif Nur Fauzi, M. Asif; Machrus, Ali (Journal of Civics and Moral Studies, 2024)
In the Indonesian economy , Micro , Small and Medium Enterprises (MSMEs) are group businesses that have the largest number , as the front guard of MSMEs has role in Indonesia and even ASEAN. Study This aim For analyze effort Arga MSME development Motorcycle Accessories and their influence to resilience economy public village . Types of research This is qualitative use? approach descriptive . Source of data obtained are primary data and secondary data . Data collection techniques with observation , interviews , and documentation . Data analysis techniques using data reduction , data exposure and withdrawal conclusion . Research result showing that effort MSME development can done with maintain quality and existence products , innovation to products , increase more market wide , and use technology so that can increase resilience economy public village